Retrospective Analysis of Bone Metabolism in Patients on Waiting List for Simultaneous Pancreas-Kidney Transplantation - Kratochvílová, Simona; Brunová, Jana; Wohl, Petr; Lánská, Věra; Saudek, František (Journal of diabetes research, 2019)
Posttransplant osteoporosis, which evolves from preexisting bone pathologies, represents a serious complication with deteriorating consequences. The aim of our study was to evaluate epidemiological data on bone mineral density (BMD) in subjects with type 1 diabetes (T1DM) in advanced stages of diabetic nephropathy indicated for simultaneous pancreas-kidney transplantation (SPK). We retrospectively compiled biochemical and densitometrical data from 177 patients with T1DM at CKD (chronic kidney disease) stages G4-G5 (115 men, 62 women, median age 40 yr, diabetes duration 23 yr) enrolled on waiting list for SPK for the first time between the years 2011 and 2016. Median Z-scores were as follows: lumbar spine (LS): -0.8 [interquartile range -1.75 to 0.1]; total hip (TH): -1.2 [-1.75 to -0.6]; femoral neck (FN): -1.2 [-1.9 to -0.7]; and distal radius (DR): -0.8 [-1.4 to -0.1]. We noted a gender difference in LS, with worse results for men (-1.1 vs. -0.3) even after adjusting for BMI (body mass index) and glomerular filtration (p < 0.001). Osteoporotic and osteopenic ranges (based on T-scores) for all major sites were 27.7% and 56.5%, respectively, with similar results across both genders. Women had a significantly higher proportion of normal BMD in LS than men (67.7 vs. 49.4%, p < 0.05). Patients with T1DM at CKD stages G4-G5 exhibited serious BMD impairment despite their young age. Men surprisingly displayed lower Z-scores and higher percentages of pathological BMD values in LS than women did. The introduction of adequate preventive measures during the advanced stages of diabetic nephropathy to prevent bone loss is recommended.
Keywords: krček femuru; diabetes mellitus 1. typu; Male; absorpční fotometrie; kosti a kostní tkáň; Bone Diseases, Metabolic; retrospektivní studie; Postoperative Complications; Waiting Lists; transplantace slinivky břišní; denzitometrie; Kidney Failure, Chronic; Risk Factors; chronické selhání ledvin; seznamy čekatelů; Osteoporosis; Adult; Densitometry; Pancreas Transplantation; dospělí; antropometrie; metabolické nemoci kostí; mužské pohlaví; pooperační komplikace; lidé středního věku; Femur Neck; osteoporóza; Anthropometry; lidé; ženské pohlaví; Kidney Transplantation; transplantace ledvin; Humans; Lumbar Vertebrae; kostní denzita; Body Mass Index; rizikové faktory; Bone Density; index tělesné hmotnosti; Diabetes Mellitus, Type 1; Retrospective Studies; Female; bederní obratle; Bone and Bones; Absorptiometry, Photon; Middle Aged